The synthesis of NiO and NiCo2O4 nanosheets by a new method and their excellent capacitive performance for asymmetric supercapacitor. (10th October 2016) - Zhang, Lixin; Zheng, Wenhui; Jiu, Hongfang; Ni, Changhui; Chang, Jianxia; Qi, Guisheng
Highlights: The NiO and NiCo2 O4 nanosheets prepared by one method called a bottom-up strategy. The morphology of two kinds of 2D materials is uniform. NiO and NiCo2 O4 nanosheets exhibited high specific capacitance. NiCo2 O4 nanosheets −based asymmetric device exhibited high energy density. Abstract: NiO and NiCo2 O4 nanosheets (NSs) were controlly prepared by one method called a bottom-up strategy employing surfactant molecular self-assembly, and followed by a thermal annealing process. The products were characterized by X-ray diffraction (XRD), a field-emission scanning electron microscope (FESEM), high resolution transmission electron microscopy (HRTEM), selected area electron diffraction (SAED), N2 adsorption-desorption (BET) and electrochemical analysis. The results reveal that the morphology of both products are all two-dimensional sheet-like and the average length and thickness of NiO and NiCo2 O4 NSs are about (220–260 nm, 9 nm) and (1 ∼ 6 μm, 28 nm), respectively. Both materials have large specific surface area and porous properties, which can increase the amount of electroactive sites and facilitate the electrolyte penetration. Hence, the NiO and NiCo2 O4 NSs exhibited excellent electrochemical performance with high specific capacitance of 407 and 876 F g −1 (1 A g −1 ), respectively, good rate performance and cycling life. Additionally, two asymmetric supercapacitors were fabricated by using the 2D porous materials NiO and NiCo2 O4 as the positive electrode, respectively, the active carbon (AC) as the negative electrode, and 6 M aqueous KOH as the electrolyte. Two asymmetric supercapacitors showed high specific capacitance and energy density of 89 F g −1 &25.99 Wh Kg −1 and 119 F g −1 &34.75Wh Kg −1, respectively.